Structural insights into the small GTPase specificity of the DOCK guanine nucleotide exchange factors. (December 2021) - Kukimoto-Niino, Mutsuko; Ihara, Kentaro; Murayama, Kazutaka; Shirouzu, Mikako
Abstract: The dedicator of cytokinesis (DOCK) family of guanine nucleotide exchange factors (GEFs) regulates cytoskeletal dynamics by activating the GTPases Rac and/or Cdc42. Eleven human DOCK proteins play various important roles in developmental processes and the immune system. Of these, DOCK1–5 proteins bind to engulfment and cell motility (ELMO) proteins to perform their physiological functions. Recent structural studies have greatly enhanced our understanding of the complex and diverse mechanisms of DOCK GEF activity and GTPase recognition and its regulation by ELMO. This review is focused on gaining structural insights into the substrate specificity of the DOCK GEFs, and discuss how Rac and Cdc42 are specifically recognized by the catalytic DHR-2 and surrounding domains of DOCK or binding partners. Highlights: The DOCK family of GEFs regulates cytoskeletal dynamics. DOCK proteins activate Rac1 and/or Cdc42 GTPases. Human DOCK proteins function in developmental processes and the immune system. This review focuses on structural insights into the substrate specificity of DOCK. Specific recognition of GTPases by DHR-2 domains is discussed.